Native and non-native teacher talk in the EFL classroom : a corpus-informed study - Nicaise, Eric (Abingdon, Oxon ; New York, NY : Routledge, 2021)
"Native and Non-Native Teacher Talk in the EFL Classroom explores and compares, both quantitively and qualitatively, the linguistic features of native and non-native English teacher talk with the aid of corpus linguistics. The basis of this book is to work towards a framework for the language that teachers of English need to be proficient in, based on an empirical study of language in the ELT classroom by both native and expert non-native users. Presenting a corpus-informed treatment of the precise linguistic features used by EFL teachers within the framework of their most common teaching functions, this book: relates directly to the teacher talk of secondary-level EFL teachers; combines quantitative and qualitative approaches to data analysis; looks into pedagogical implications for ELT and proposes a flexible language development model based on the evidence from the classroom for initial teacher education and teacher development programmes; Provides a corpus-based repertoire of language for the classroom which is of relevance to native and non-native student-teachers and practicing teachers. By analysing attested examples of teacher talk from English language classes where the teachers teach their native language, and EFL classes where francophone EFL teachers teach English, this book raises both groups of teachers' awareness of the type of language they use which might provide a model for the students. This volume is also of relevance to student-teachers in that it highlights the need for much greater awareness of the impact of language use in both learning and teaching. It is a major resource for MA TESOL and MA Applied Linguistics modules, such as classroom discourse, corpus linguistics and ELT, English for professional purposes and teaching placement preparation"--
OCLC-licensed vendor bibliographic record.
Keywords: English language -- Study and teaching (Secondary) -- Foreign speakers; Language teachers -- Training of; LANGUAGE ARTS & DISCIPLINES / General; LANGUAGE ARTS & DISCIPLINES / Linguistics